2005
DOI: 10.1055/s-0038-1632931
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in canine immune-mediated polyarthritis and osteoarthritis

Abstract: The purpose of this study was to determine the cytokine profile in 21 dogs with canine immune-mediated polyarthritis (IMA) and 15 dogs with osteoarthritis (OA) caused by cranial cruciate ligament rupture (CCLR). The mRNA expression of interleukin (IL)-1alpha, IL-1beta, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-18, interferon (IFN)-gamma, transforming growth factor (TGF)-beta, and tumour necrosis factor (TNF)-alpha were analysed in synovial fluid by semi-quantitative RT-PCR, while TNF-alpha protein was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…It is therefore possible that TNF-α production is increased in dogs treated with CsA. TNF-α is a proinflammatory cytokine and considered to be an important effector molecule in the pathogenesis of IBD and immune-mediated polyarthritis [13,27]. Although a previous clinical study reported that CsA appeared to be effective in dogs with IBD that were refractory to steroids [1], the results of the present study indicate that CsA should be used with care for the treatment of TNF-α-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that TNF-α production is increased in dogs treated with CsA. TNF-α is a proinflammatory cytokine and considered to be an important effector molecule in the pathogenesis of IBD and immune-mediated polyarthritis [13,27]. Although a previous clinical study reported that CsA appeared to be effective in dogs with IBD that were refractory to steroids [1], the results of the present study indicate that CsA should be used with care for the treatment of TNF-α-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials have produced evidence to support the use of CsA for IBD and rheumatoid arthritis in humans [8,25]. In dogs, TNF-α has been indicated to play an important role in the pathogenesis of IBD and immune-mediated polyarthritis [13,27]. However, the effect of CsA on TNF-α mRNA expression has not been evaluated in dogs.…”
mentioning
confidence: 99%
“…In previous reports, TNF a and IL-4 were also found present in osteoarthritic synovial fluid, 15,16 and they were thought to be potent fibroblast chemoattractants inducing migration. 17,18 These reports support our results that merely inhibiting TGFb did not fully reverse the increase of cell expansion in synovial fluid.…”
Section: Synovial Fluid Enhances Migration Of Mscsmentioning
confidence: 99%
“…These signals augment destruction, thus promoting the harmful cycle. No single cytokine is the sole mediator of joint damage, and the adverse effects are likely the result of a complex interaction of cytokines (Fernandes et al, 2002;Hegemann et al, 2005;Hulejová et al, 2007), proteolytic enzymes (Borzi et al, 2000), leukocytes (Sandell et al, 2008), synoviocytes (Villiger et al, 1992) and chondrocytes (Kuroki et al).…”
Section: Introductionmentioning
confidence: 99%